Population dynamics of Scomberomorus brasiliensis from a small-scale fishery off Southern Brazil (Ocean and Coastal Research, 2024)
Scomberomorus brasiliensis is the most important fish species of the small-scale fishery off the southwestern Atlantic northof the La Plata estuary. For management purposes, this study evaluated their reproductive biology, size, age and growthalong the Paraná coast. Monthly samples (March 2018-June 2020) from the fishery comprised 933 specimens (413 males,520 females), 210-779 mm fork length, corresponding to a size smaller than in the northern areas. It presented negativeallometry (b = 2.69159, length-weight relationship). Specimens in all stages of maturity occurred during the study period,indicating spawning in the area from October to June, peaking from January to March. The gonad–length relationship wassuitable to confirm this assessment. Individual fecundity varied between 34,484 and 390,786 oocytes. Maturity occurredat L50 = 446.46 mm, t50 = 1.4 years, and L100 = 588.79 mm, and t100 = 2.3 years. The growth parameters were L∞ = 771.68 mm,k = 0.65 year-1 and t0 = -0.102 years, with cohorts aged from 0.5 to 6.5 years. Scomberomorus brasiliensis along the Paranácoast constitutes a self-sustaining group, not directly related to that from northeastern Brazil. This small-scale fishery is notcurrently negatively affecting stock level; it is essential to monitor these attributes to detect future changes or impacts.